Copper-aluminum eutectic composite conductive bar for strong heat dissipation transformer and manufacturing method thereof

CN123017707APending Publication Date: 2026-10-30CIXI CHIMA METAL PRODUCTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611174408.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有铜铝复合导电排技术在实际变压器应用中存在以下严重缺陷:其一,铜铝界面结合强度不足,热循环工况下易分层剥离

Benefits of technology

[0025]与现有技术相比,采用该技术方案所达到的技术效果:S100步骤通过在真空条件下熔炼和铸轧制备铜铝共晶复合板坯,真空环境避免了熔炼过程中金属氧化夹杂的生成,保证了共晶熔体的纯净度和复合界面的结合质量,S200步骤通过一次退火、冷轧、二次退火、精轧和终退火的多级热处理与轧制工艺,有效消除了铸轧和冷轧过程中产生的残余应力,促进了铜铝界面共晶层的稳定化和组织均匀化,使界面结合强度得到显著提升,S300步骤在铝层一侧表面加工形成散热齿赋予导电排强化散热功能,使得散热结构与导电排本体形成一体化构造,避免了额外加装散热部件的装配成本和界面热阻,S400步骤将导电排组固定于立体绝缘承载架的对应安装台上并确保散热齿与风道的气流方向相对应,保证了组装精度和散热通道的对准,整个制造工艺流程完整可控,各步骤之间衔接紧密,适合工业化批量生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017707A_ABST
    Figure CN123017707A_ABST
Patent Text Reader

Abstract

The present application relates to transformer components and power distribution material technical field, especially to a kind of copper-aluminum eutectic composite conductive bar for strong heat dissipation transformer and manufacturing method thereof.A kind of copper-aluminum eutectic composite conductive bar for strong heat dissipation transformer is disclosed, comprising: three-dimensional insulating bearing frame and the conductive bar group on it, three-dimensional insulating bearing frame includes the air duct being set along its body through;Conductive bar group includes copper layer, copper-aluminum eutectic metallurgical bonding layer and aluminium layer in turn from bottom to top, copper layer is located at the side close to three-dimensional insulating bearing frame, at least part of the side surface of aluminium layer away from copper-aluminum eutectic metallurgical bonding layer is provided with heat dissipation tooth, heat dissipation tooth is formed by the outward bulging of aluminium layer body, heat dissipation tooth corresponds with the airflow direction of air duct, to supply copper-aluminum eutectic composite conductive bar heat dissipation.The interface stability of the copper-aluminum eutectic composite conductive bar of the present application is excellent during long-term thermal cycle operation, local temperature rise is significantly reduced compared with traditional flat plate arrangement pure copper conductive bar, greatly delays the thermal aging of transformer insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of transformer components and power distribution materials, and in particular to a copper-aluminum eutectic composite busbar for high heat dissipation transformers and its manufacturing method. Background Technology

[0002] In the field of transformer manufacturing and high-current transmission, busbars, as the core current-carrying components connecting transformer windings to external lines, directly determine the transformer's current-carrying capacity, operational safety, and service life through their material selection, interface bonding quality, and heat dissipation performance. With the rapid development of modern transformers towards larger capacity and more compact designs, busbars need to withstand larger operating currents, more frequent thermal cycling shocks, and more stringent temperature rise limits. This places significantly higher demands on the overall performance of busbars than under traditional operating conditions.

[0003] To balance conductivity, weight, and cost, copper-aluminum composite busbars have become an important development direction in the industry. Copper has excellent conductivity and low contact resistance, but its high density and cost make it expensive; aluminum has low density and low cost, but its surface is prone to oxidation, leading to increased contact resistance. The copper-aluminum composite structure aims to leverage the complementary advantages of the two materials, with the copper layer providing electrical contact to ensure low contact resistance, and the aluminum layer providing the main conductive function to achieve lightweighting and cost control. However, existing copper-aluminum composite busbar technologies have the following serious drawbacks in practical transformer applications: First, the bonding strength at the copper-aluminum interface is insufficient, making it prone to delamination under thermal cycling conditions. Existing technologies mostly use cold rolling, cladding welding, or explosive welding processes to produce copper-aluminum composite busbars. These processes essentially rely on mechanical pressure to press the copper and aluminum layers together, achieving a solid-phase mechanical bond rather than a true metallurgical bond. Although mechanical pressure can activate some atoms at the interface to form interatomic bonds, the thickness of the bonding layer is extremely limited, and the interfacial bonding strength is generally low. During the frequent switching between full load and no load in a transformer, the busbars are subjected to severe thermal expansion and contraction as well as electrodynamic impacts. The linear expansion coefficients of copper and aluminum differ significantly (copper is approximately 16.6 × 10⁻⁻⁻⁴). 6 / ℃, aluminum is approximately 23.2×10⁻ 6The copper-aluminum composite busbar (C-Aluminum) exhibits a high thermal stress at its interface (temperature range of ℃ / °C). When the interface bonding strength is insufficient to resist this thermal stress, the copper-aluminum interface is prone to differential plastic deformation, leading to interface cracking, blistering, or delamination. After delamination, the internal resistance of the busbar increases sharply, exacerbating localized heating and creating a vicious cycle that seriously threatens the safe operation of the transformer. Secondly, there is a lack of systematic thermal management and enhanced heat dissipation design. Regardless of the composite process used, existing copper-aluminum composite busbars still use the traditional flat rectangular cross-section design, merely replacing the material without fully utilizing the ease of processing and forming of aluminum-based materials for systematic thermal management optimization. Under high current conditions, the heat generated by the busbar increases proportionally to the square of the current, while the effective heat dissipation area of ​​traditional flat busbars is limited to the upper and lower main planes, resulting in extremely limited convective heat dissipation efficiency. In the high-temperature oil-immersed or dry-type environments of compact transformers, the problem of insufficient heat dissipation area is even more pronounced. Excessive localized temperature rise of the busbar accelerates the thermal aging of the transformer insulation material, significantly shortening the transformer's service life. While some solutions have attempted to improve heat dissipation by creating heat dissipation slits on the sides of the copper-aluminum busbars, the increase in heat dissipation area is limited, and the lack of coordinated design with airflow channels makes it difficult to form an efficient directional heat dissipation path. Thirdly, existing three-dimensional arrangement schemes for copper-aluminum composite busbars are complex, resulting in severe interphase thermal interference. In the arrangement design of three-phase busbars in transformers, traditional schemes typically place the three busbars in the same plane, using complex "U"-shaped or "U"-shaped nested cuts to avoid terminals. This planar arrangement not only significantly increases the bending and processing difficulty of the copper-aluminum composite plate, but more seriously, the heat generated by the lower busbars directly rises and bakes the upper busbars, causing interphase thermal interference and heat superposition, further exacerbating the overall temperature rise problem.

[0004] In summary, existing busbar technologies struggle to simultaneously meet the comprehensive requirements of "low contact resistance, high interfacial bonding strength, high heat dissipation efficiency, lightweight design, and low cost." A novel composite structure and molding scheme is urgently needed that can fundamentally address the issues of insufficient copper-aluminum interfacial bonding strength and easy delamination during thermal cycling, while also achieving efficient heat dissipation and a three-dimensional staggered arrangement through structural design, thereby overcoming current technological bottlenecks. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a copper-aluminum eutectic composite busbar for high-heat-dissipation transformers and its manufacturing method. It uses a copper-aluminum eutectic metallurgical bonding layer to replace the traditional mechanical composite interface, resulting in excellent interface stability during long-term thermal cycling. Cold air enters from the lower part of the support frame and flows upward, exiting after passing through the heat dissipation tooth area, forming a bottom-up "chimney effect" to enhance the convective heat dissipation path. Under high-current full-load conditions, the local temperature rise is significantly lower than that of traditional flat-plate pure copper busbars, greatly delaying the thermal aging of transformer insulation materials.

[0006] Therefore, the first objective of this invention is to provide a copper-aluminum eutectic composite busbar for a high-heat-dissipation transformer.

[0007] The second objective of this invention is to provide a method for manufacturing a copper-aluminum eutectic composite busbar for a high-heat-dissipation transformer.

[0008] To achieve the first objective of this invention, the technical solution of this invention provides a copper-aluminum eutectic composite conductive busbar for a high-heat-dissipation transformer, comprising: a three-dimensional insulating support frame and a conductive busbar assembly disposed thereon; the three-dimensional insulating support frame includes an air duct that runs through its body; the conductive busbar assembly comprises, from bottom to top, a copper layer, a copper-aluminum eutectic metallurgical bonding layer and an aluminum layer; the copper layer is disposed on the side close to the three-dimensional insulating support frame; at least a portion of the surface of the aluminum layer away from the copper-aluminum eutectic metallurgical bonding layer is provided with heat dissipation teeth, which are formed by protruding outward from the aluminum layer body; the heat dissipation teeth correspond to the airflow direction of the air duct to dissipate heat from the copper-aluminum eutectic composite conductive busbar.

[0009] Furthermore, the present invention provides a copper-aluminum eutectic composite busbar for a high-heat-dissipation transformer, which can be used in oil-immersed transformers, dry-type transformers, reversible contactors, or high-current power transmission systems.

[0010] Compared with existing technologies, the technical effects achieved by this solution are as follows: The three-dimensional insulating support frame provides a stable installation foundation for the busbar assembly, and the through-type air duct provides a directional flow channel for heat dissipation airflow, allowing cold air to flow along a preset path across the surface of the busbar to achieve forced convection heat dissipation. The busbar assembly consists of a three-layer composite structure from bottom to top, consisting of a copper layer, a copper-aluminum eutectic metallurgical bonding layer, and an aluminum layer. The copper layer ensures low contact resistance and high conductivity during overlap. The copper-aluminum eutectic metallurgical bonding layer achieves atomic-level metallurgical bonding between copper and aluminum, completely avoiding the defects of insufficient interface bonding strength and easy delamination in traditional mechanical composite methods. At least part of the surface of the aluminum layer away from the eutectic metallurgical bonding layer is provided with heat dissipation teeth, which are formed by protruding outward from the aluminum layer body. This one-piece molding structure not only ensures no interface thermal resistance between the heat dissipation teeth and the aluminum layer, but also makes full use of the lightweight heat dissipation advantages of aluminum material with low density and high thermal conductivity. The heat dissipation teeth correspond to the airflow direction of the air duct, forming an efficient enhanced convection heat dissipation path, effectively reducing the local temperature rise of the busbar under high current conditions.

[0011] In one technical solution of the present invention, the thickness of the conductive busbar is 5mm-20mm, the thickness of the copper layer is 1mm-4mm, the thickness of the aluminum layer is 4mm-16mm, and the thickness of the copper-aluminum eutectic metallurgical bonding layer is 1μm-50μm.

[0012] Compared with existing technologies, the technical effects achieved by this solution are as follows: The total thickness of the busbar assembly is limited to 5mm to 20mm, which ensures sufficient conductive cross-sectional area to carry large currents while avoiding material waste and bending difficulties caused by excessive thickness. The copper layer thickness is limited to 1mm to 4mm, which ensures sufficient copper material thickness on the electrical contact side to guarantee low contact resistance and wear resistance, while controlling the amount of copper material within a reasonable range to reduce material costs. The aluminum layer thickness is limited to 4mm to 16mm, which gives the busbar body sufficient conductive cross-sectional area, while the low density of aluminum significantly reduces the overall weight of the busbar. The thickness of the copper-aluminum eutectic metallurgical bonding layer is limited to 1μm to 50μm, which ensures sufficient thickness of the eutectic layer to achieve a strong atomic-level metallurgical bond, while avoiding the problem of increased brittleness caused by excessive thickness of the eutectic layer. The synergistic optimization of the thickness of each layer allows the busbar to achieve a balance between conductivity, mechanical strength and lightweight.

[0013] In one technical solution of the present invention, the bottom of the heat dissipation denticle retains a continuous aluminum base layer with a thickness of not less than 2mm, the height of the heat dissipation denticle is 2mm-8mm, the number of heat dissipation denticles is multiple, and the spacing between adjacent heat dissipation denticles is 2mm-10mm.

[0014] Compared with existing technologies, the technical effects achieved by this solution are as follows: The bottom of the heat dissipation fins retains a continuous aluminum base layer of at least 2mm thickness, ensuring sufficient conductive cross-sectional area for the conductive busbar during high current transmission. This avoids excessive reduction of the conductive cross-section and increased resistance caused by processing the heat dissipation fins. The height of the heat dissipation fins is limited to 2mm to 8mm, ensuring sufficient height to increase the heat exchange surface area and create turbulent flow for enhanced heat transfer, while avoiding processing difficulties, reduced structural strength, and material waste caused by excessive fin height. Multiple heat dissipation fins are arranged at intervals along the aluminum layer surface, creating gaps between adjacent fins for airflow. The spacing between adjacent fins is limited to 2mm to 10mm, ensuring sufficient gaps to avoid obstructing airflow and guaranteeing a sufficient number of fins per unit width for heat exchange. This spacing range also ensures that the heat dissipation fins will not deform or break during processing due to insufficient spacing.

[0015] In one technical solution of the present invention, the shear strength of the copper-aluminum eutectic metallurgical bonding layer is ≥75MPa and the peel strength is ≥140N / mm.

[0016] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the shear strength of the copper-aluminum eutectic metallurgical bonding layer is not less than 75 MPa and the peel strength is not less than 140 N / mm. The limitation of these two mechanical performance indicators ensures that the eutectic bonding layer has sufficient structural reliability under the complex service conditions of the transformer. The shear strength indicator ensures that the conductive bar will not undergo interlayer slip when bearing the interfacial shear stress generated by thermal expansion and cold contraction. The peel strength indicator ensures that the conductive bar will not suffer from interfacial cracking when bearing the peel stress generated by electrodynamic force impact and bending deformation. The interfacial bonding strength, which is much higher than that of the traditional cold-rolled mechanical composite bar, enables the conductive bar to maintain the integrity of the interfacial structure for a long time under the frequent full-load and no-load switching conditions of the transformer, and the interfacial internal resistance remains stable throughout the full life cycle, thereby avoiding the problems of local heating and insulation aging caused by interface delamination.

[0017] In one technical solution of the present invention, the conductive bar set is in a "several" shape, two ends of the conductive bar set are connected to the three-dimensional insulating bearing frame through bolts, and the heat dissipation fins are arranged at the middle part of the conductive bar set.

[0018] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the spatial bent structure of the conductive bar set in a "several" shape enables the two ends of the conductive bar to be on the same horizontal plane, which facilitates bolt connection with the three-dimensional insulating bearing frame. Meanwhile, the structure with the middle part arched upwards increases the contact area between the conductive bar and the surrounding air. The two ends of the conductive bar set are connected to the three-dimensional insulating bearing frame through bolts, which ensures firm and reliable connection between the conductive bar and the bearing frame and facilitates installation, disassembly and maintenance. The heat dissipation fins arranged at the middle part of the conductive bar set make the heat dissipation fins located in the region with the highest temperature of the conductive bar, because the middle part is the region with the longest current path and far away from the heat dissipation paths at the two ends. Arranging the heat dissipation fins at this position can achieve the most effective temperature rise suppression. Meanwhile, no heat dissipation fins are arranged in the connection regions at the two ends, which ensures the flatness of the connection end faces and the reliability of bolt connection.

[0019] In one technical solution of the present invention, the conductive bar set includes a first conductive bar, a second conductive bar and a third conductive bar. The three-dimensional insulating bearing frame is provided with a first mounting table, a second mounting table and a third mounting table along the width direction, the first mounting table, the second mounting table and the third mounting table are sequentially elevated in a stepwise manner, and the first conductive bar, the second conductive bar and the third conductive bar are respectively arranged on the first mounting table, the second mounting table and the third mounting table.

[0020] Compared with existing technologies, the technical effects achieved by this solution are as follows: The busbar assembly includes a first busbar, a second busbar, and a third busbar, which correspond to the three-phase input terminals of the transformer, respectively. The three-dimensional insulating support frame is provided with a first mounting platform, a second mounting platform, and a third mounting platform along the width direction, and the three mounting platforms are raised in a stepped manner. This stepped staggered arrangement structure completely isolates the three-phase busbars in terms of spatial height. The first busbar, the second busbar, and the third busbar are set on three mounting platforms at different elevations, which completely avoids the problem of interphase thermal interference caused by the heat generated by the lower busbar directly rising and baking the upper busbar in the traditional planar arrangement. At the same time, the staggered spatial arrangement also avoids the risk of accidental electrical contact between the busbars. The air circulation paths around each busbar do not interfere with each other, further improving the overall heat dissipation efficiency.

[0021] In one technical solution of the present invention, the air duct includes a first air duct, a second air duct and a third air duct, which are arranged sequentially along the width direction of the three-dimensional insulating support frame, and the thickness of the first air duct, the second air duct and the third air duct increases sequentially.

[0022] Compared with existing technologies, the technical effects achieved by this solution are as follows: The air ducts include a first air duct, a second air duct, and a third air duct, corresponding to the first, second, and third conductive bars, respectively. The three air ducts are arranged sequentially along the width of the three-dimensional insulating support frame, so that the heat dissipation airflow channels under each conductive bar are independent and do not interfere with each other. The thickness of the first, second, and third air ducts increases sequentially, matching the stepped rise structure of the three mounting platforms. This ensures that the air outlet of each air duct is directly facing the heat dissipation tooth area of ​​the corresponding conductive bar, guaranteeing that the cold air entering from the bottom of each air duct can directly scour the heat dissipation tooth area of ​​the corresponding conductive bar, and that the airflow will not bypass the heat dissipation tooth area due to misalignment of the air ducts. This one-to-one correspondence air duct layout allows each phase conductive bar to obtain independent and sufficient cooling airflow, avoiding the problems of airflow competition and uneven heat dissipation caused by sharing air ducts between phase conductive bars.

[0023] To achieve the second objective of the present invention, the technical solution of the present invention provides a method for manufacturing a copper-aluminum eutectic composite conductive bar for a high heat dissipation transformer, which is used for manufacturing the copper-aluminum eutectic composite conductive bar according to any one of the above technical solutions, and comprises the following steps: S100, preparing a copper-aluminum eutectic composite slab: preparing materials according to the target thickness ratio of the copper layer to the aluminum layer, heating the aluminum raw material to melting under a vacuum condition, refining and holding the temperature to a first temperature, performing surface degreasing and texturing treatment on the copper strip raw material and preheating to a second temperature, pouring the aluminum liquid at the first temperature onto one side of the copper strip raw material for cast rolling, and controlling the cooling rate to form an initial composite slab; S200, multi-stage heat treatment and rolling: placing the initial composite slab in a protective atmosphere for primary annealing, holding the temperature for a first time; then performing cold rolling processing and secondary annealing treatment, holding the temperature for a second time; then performing finish rolling, leveling and sizing processing to a target thickness, then performing final annealing treatment, discharging from the furnace and air-cooling to room temperature to obtain a second composite slab; S300, heat dissipation tooth processing: processing and forming heat dissipation teeth on the surface of the aluminum layer side of the second composite slab to obtain a conductive bar group; S400, assembling: fixing the conductive bar group on the corresponding mounting table of the three-dimensional insulating carrier, so that the heat dissipation teeth correspond to the airflow direction of the air duct.

[0024] Further, the method for manufacturing the copper-aluminum eutectic composite conductive bar further comprises: bending forming: slitting the composite slab processed with the heat dissipation teeth and bending it into a "几"-shaped three-dimensional bending structure by using numerical control bending equipment, wherein the copper layer side is taken as the inner side and the aluminum layer side is taken as the outer side during bending; end interface processing: processing a connection structure at the connection end of the copper layer of the conductive bar, and performing chamfering treatment on the end and the edge.

[0025] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: in step S100, the copper-aluminum eutectic composite slab is prepared by smelting and cast rolling under vacuum conditions, the vacuum environment avoids the formation of metal oxide inclusions during the smelting process, and ensures the purity of the eutectic melt and the bonding quality of the composite interface; in step S200, through the multi-stage heat treatment and rolling process of primary annealing, cold rolling, secondary annealing, finish rolling and final annealing, the residual stress generated in the cast rolling and cold rolling processes is effectively eliminated, the stabilization and structure homogenization of the eutectic layer at the copper-aluminum interface are promoted, and the interface bonding strength is significantly improved; in step S300, heat dissipation teeth are formed on the surface of the aluminum layer side to endow the conductive bar with an enhanced heat dissipation function, so that the heat dissipation structure and the conductive bar body form an integrated structure, which avoids the assembly cost and interface thermal resistance of additionally installing heat dissipation components; in step S400, the conductive bar group is fixed on the corresponding mounting table of the three-dimensional insulating carrier and the heat dissipation teeth are ensured to correspond to the airflow direction of the air duct, which ensures the assembly accuracy and the alignment of the heat dissipation channels. The whole manufacturing process flow is complete and controllable, the connection between each step is tight, and the method is suitable for industrial mass production.

[0026] In one technical solution of the present invention, in S100: the first temperature is 720℃-750℃; the second temperature is 100℃-150℃; and the cooling rate is 300℃ / s-1000℃ / s.

[0027] Furthermore, in S100: the aluminum raw material is made of 1060 aluminum alloy with an aluminum content ≥99.2%; the copper strip raw material is made of pure copper strip with a conductivity ≥97% IACS.

[0028] Furthermore, in S100: the initial thickness of the roll gap in the cast-rolled material is 2.0 mm to 5.0 mm.

[0029] Compared with existing technologies, the technical effects achieved by this solution are as follows: Limiting the first temperature of the molten aluminum to 720℃ to 750℃ ensures sufficient fluidity and wettability for uniform spreading on the copper strip surface, while avoiding excessive oxidation and increased energy consumption due to excessively high temperatures. Limiting the second temperature of the copper strip preheating to 100℃ to 150℃ effectively improves the activity of the copper strip surface, enhances the interfacial wettability between the molten aluminum and the copper strip, and facilitates the full occurrence of the eutectic reaction at the interface. The high cooling rate of 300℃ / s to 1000℃ / s during casting and rolling allows the molten aluminum to rapidly crystallize on the copper strip surface, refining the grain size of the eutectic structure, avoiding the precipitation of coarse and brittle phases, and ensuring the density and uniformity of the eutectic bonding layer. The synergistic control of these process parameters effectively guarantees the interfacial bonding quality and microstructure uniformity of the copper-aluminum eutectic composite slab.

[0030] In one technical solution of the present invention, in S200: the temperature of the first annealing is 250℃-300℃, and the first time is 2h-5h; the temperature of the second annealing is 300℃-350℃, and the second time is 1h-3h.

[0031] Furthermore, in S200: cold rolling is carried out in three passes, with the deformation amount in a single pass controlled at 20%-35%, and 2-5 finishing rolling passes are performed.

[0032] Compared with existing technologies, the technical effects achieved by this solution are as follows: The primary annealing temperature is limited to 250℃ to 300℃ and held for 2 to 5 hours, which effectively eliminates the internal residual stress generated during casting and rolling, promotes element diffusion at the copper-aluminum interface and the initial formation of the eutectic layer, and provides a slab with stable structure and sufficient stress release for subsequent cold rolling. The secondary annealing temperature is limited to 300℃ to 350℃ and held for 1 to 3 hours. This temperature range is higher than the primary annealing temperature, which allows the eutectic layer that was broken during cold rolling to re-fusion and heal, further improving the continuity and density of the eutectic bonding layer. The gradient design of the two annealing temperatures allows the eutectic structure to undergo a complete structural evolution process from formation, breakage to re-fusion, ultimately forming a uniform thickness and firmly bonded atomic-level metallurgical bonding layer. This multi-stage annealing process also avoids the problems of excessive grain growth and performance degradation that may be caused by single high-temperature long-term annealing, and takes into account the optimization of interface bonding strength and overall material mechanical properties.

[0033] The technical solution provided by this invention can achieve at least one of the following effects: (1) The copper-aluminum eutectic metallurgical bonding layer achieves atomic-level metallurgical bonding between the copper layer and the aluminum layer. The interface shear strength is not less than 75MPa and the peel strength is not less than 140N / mm, which is much higher than the interface bonding strength of traditional cold-rolled mechanical composite busbars. Under the high-frequency thermal expansion and contraction of transformers and short-circuit electrodynamic impact conditions, there is no delamination, peeling or blistering. The interface internal resistance remains stable throughout the entire life cycle, which fundamentally solves the common industry problem of insufficient interface bonding strength and easy delamination during thermal cycling of traditional copper-aluminum composite busbars. (2) By integrally forming heat dissipation teeth on the surface of the aluminum layer and cooperating with the air ducts that are set through the interior of the three-dimensional insulating support frame, the heat dissipation teeth are formed by protruding outward from the aluminum layer body and are corresponding to the airflow direction of the air duct. Cold air flows from bottom to top through the gaps between the heat dissipation teeth to form a chimney effect to enhance convective heat dissipation. The effective heat exchange area is significantly increased compared with the traditional flat conductive busbar. The local temperature rise under high current full load conditions is significantly reduced, which greatly delays the thermal aging of the transformer insulation material and significantly improves the operating reliability and service life of the transformer. (3) The first, second and third conductive bars are completely isolated in space by three step-like mounting platforms that rise in sequence. With the independent air ducts corresponding to each conductive bar, the problem of interphase heat radiation and mutual interference of hot air in the traditional planar arrangement is completely avoided. At the same time, the conductive bars have a zigzag spatial bending structure that does not require complex planar opening nesting and cutting, which greatly reduces the processing difficulty and manufacturing cost. (4) Through the precise functional zoning of the copper-aluminum eutectic composite structure, the copper layer is responsible for the electrical connection with low contact resistance while the aluminum layer is responsible for the main body conduction and integrated heat dissipation. Under the premise of ensuring the same current carrying capacity and extremely low lap contact resistance, the overall weight of the busbar is significantly reduced and the amount of expensive copper material is effectively controlled. The manufacturing process is complete and controllable and has good process compatibility with the existing copper-aluminum composite busbar production line. It can be industrialized without large-scale equipment modification and has strong industrial promotion value. Attached Figure Description

[0034] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be discussed below. Obviously, the technical solutions described in conjunction with the accompanying drawings are only some embodiments of the present invention. For those skilled in the art, other embodiments and their accompanying drawings can be obtained based on the embodiments shown in these drawings without creative effort.

[0035] Figure 1 This is one of the structural schematic diagrams of the copper-aluminum eutectic composite conductive bus of the present invention; Figure 2 This is the second schematic diagram of the structure of the copper-aluminum eutectic composite conductive bus of the present invention; Figure 3 This is one of the structural schematic diagrams of the conductive busbar of the present invention; Figure 4 This is the third schematic diagram of the structure of the copper-aluminum eutectic composite conductive bus of the present invention; Figure 5 This is a cross-sectional view along direction A of the third schematic diagram of the copper-aluminum eutectic composite conductive busbar of the present invention; Figure 6 This is the second schematic diagram of the conductive busbar of the present invention.

[0036] Explanation of reference numerals in the attached figures: 10. Conductive busbar assembly; 11. Copper layer; 12. Copper-aluminum eutectic metallurgical bonding layer; 13. Aluminum layer; 14. Heat dissipation fins; 15. First conductive busbar; 16. Second conductive busbar; 17. Third conductive busbar; 20. Three-dimensional insulating support frame; 21. Air duct; 211. First air duct; 212. Second air duct; 213. Third air duct. Detailed Implementation

[0037] The technical solutions of various embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] The following reference Figures 1 to 6 The technical solutions of some embodiments of the present invention are described below.

[0039]

Example 1

[0040] The manufacturing method of this embodiment is as follows: S100. Preparation of copper-aluminum eutectic composite slab: Prepare materials according to the target thickness ratio of copper layer and aluminum layer. Heat 1060 aluminum ingot to 730℃ under vacuum conditions to melt and refine and hold for 40 minutes. Degrease and brush the surface of T2 copper strip and preheat to 130℃. Pour molten aluminum at 730℃ onto one side of copper strip under static pressure and cast and roll. Cooling rate is 600℃ / s to form initial composite slab. S200, multi-stage heat treatment and rolling: The initial composite slab is placed in a protective atmosphere and annealed at 280℃ for 3 hours; then it is cold rolled and annealed at 320℃ for 2 hours; then it is finished rolled, leveled and cut to length to the target thickness of 12mm, and then annealed in the final stage, and air-cooled to room temperature after being taken out of the furnace. S300, Heat dissipation tooth processing: Multiple heat dissipation teeth 14 are formed by milling in the middle area of ​​the aluminum layer side surface of the second composite plate. The height of the heat dissipation teeth is 5mm, the spacing between adjacent heat dissipation teeth is 5mm, and a 2mm thick continuous aluminum base layer is retained at the bottom; heat dissipation teeth are not processed in the connection area of ​​the conductive bus end and the installation area that is in contact with the insulating support frame. S400 Assembly: After bending and forming, the first conductive bar 15, the second conductive bar 16 and the third conductive bar 17 are respectively fixed on the first mounting platform, the second mounting platform and the third mounting platform of the three-dimensional insulating support frame 20, so that the height direction of the heat dissipation teeth 14 is consistent with the airflow direction of the corresponding air duct.

[0041] Testing revealed that the copper-aluminum eutectic composite conductive busbar prepared in this embodiment exhibited a shear strength of 88 MPa and a peel strength of 155 N / mm for the copper-aluminum eutectic metallurgical bonding layer. No delamination, peeling, or blistering was observed during thermal cycling tests from -40℃ to 150℃ and under high-current short-circuit electrodynamic impact. The overall weight was reduced by 45% compared to traditional pure copper conductive busbars, resulting in a material cost reduction of approximately 30%. Temperature rise tests conducted according to GB / T1094.2 standard showed that, under rated current conditions, the temperature rise in the central heat dissipation area of ​​the conductive busbar was 52 K, 26 K lower than the 78 K temperature rise of a traditional flat pure copper conductive busbar of the same specifications, representing a 33% reduction. Infrared thermal imaging measurements of the conductive busbar surface temperature distribution showed uniform temperature distribution in the heat dissipation tooth area, with a temperature difference of no more than 2 K between adjacent heat dissipation teeth. This indicates that the airflow channel between the heat dissipation teeth and the air duct is unobstructed, allowing cold air to effectively flow through the gaps between the heat dissipation teeth for uniform heat dissipation.

[0042]

Example 2

[0043]

Example 3

[0044]

Example 4

[0045]

Example 5

[0046]

Example 6

[0047]

Example 7

[0048]

Example 8

[0049] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered illustrative and non-limiting in all respects. The scope of the invention is defined by the appended claims, not by the foregoing description, and thus all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0050] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A copper-aluminum eutectic composite busbar for a high-heat-dissipation transformer, characterized in that, comprising: a three-dimensional insulating carrier (20) and a conductive bar set (10) disposed thereon, wherein the three-dimensional insulating carrier (20) comprises an air duct (21) penetrating through the body thereof; the conductive bar set (10) sequentially comprises a copper layer (11), a copper-aluminum eutectic metallurgical bonding layer (12) and an aluminum layer (13) from bottom to top, the copper layer (11) is disposed on the side close to the three-dimensional insulating carrier (20), at least part of the surface of the side of the aluminum layer (13) away from the copper-aluminum eutectic metallurgical bonding layer (12) is provided with heat dissipation fins (14), the heat dissipation fins (14) are formed by protruding outward from the body of the aluminum layer (13), and the heat dissipation fins (14) correspond to the air flow direction of the air duct (21), so as to dissipate heat of the copper-aluminum eutectic composite conductive bar.

2. The copper-aluminum eutectic composite conductive bus according to claim 1, characterized in that, The thickness of the conductive bar set (10) is 5mm-20mm, the thickness of the copper layer (11) is 1mm-4mm, the thickness of the aluminum layer (13) is 4mm-16mm, and the thickness of the copper-aluminum eutectic metallurgical bonding layer (12) is 1μm-50μm.

3. The copper-aluminum eutectic composite conductive bus according to claim 1, characterized in that, A continuous aluminum base layer with a thickness of no less than 2mm is retained at the bottom of the heat dissipation fins (14), the height of the heat dissipation fins (14) is 2mm-8mm, the number of the heat dissipation fins (14) is multiple, and the spacing between adjacent heat dissipation fins (14) is 2mm-10mm.

4. The copper-aluminum eutectic composite conductive bus according to claim 1, characterized in that, The shear strength of the copper-aluminum eutectic metallurgical bonding layer (12) is ≥75MPa, and the peel strength is ≥140N / mm.

5. The copper-aluminum eutectic composite conductive bus according to claim 1, characterized in that, The conductive bar set (10) is in a "several" shape, two ends of the conductive bar set (10) are connected to the three-dimensional insulating carrier (20) through bolts, and the heat dissipation fins (14) are arranged in the middle of the conductive bar set (10).

6. The copper-aluminum eutectic composite conductive bus according to claim 1, characterized in that, The conductive bar set (10) comprises a first conductive bar (15), a second conductive bar (16) and a third conductive bar (17), the three-dimensional insulating carrier (20) is provided with a first mounting table, a second mounting table and a third mounting table along the width direction, the first mounting table, the second mounting table and the third mounting table are sequentially elevated in a stepwise manner, and the first conductive bar (15), the second conductive bar (16) and the third conductive bar (17) are respectively arranged on the first mounting table, the second mounting table and the third mounting table.

7. The copper-aluminum eutectic composite conductive bus according to claim 6, characterized in that, The air duct (21) comprises a first air duct (211), a second air duct (212) and a third air duct (213), the first air duct (211), the second air duct (212) and the third air duct (213) are sequentially arranged along the width direction of the three-dimensional insulating carrier (20), and the thicknesses of the first air duct (211), the second air duct (212) and the third air duct (213) are sequentially increased.

8. A method for manufacturing a copper-aluminum eutectic composite busbar for a high-heat-dissipation transformer, characterized in that, A method for manufacturing the copper-aluminum eutectic composite conductive bar according to any one of claims 1 to 7, comprising the following steps: S100. Preparation of copper-aluminum eutectic composite slab: Prepare materials according to the target thickness ratio of copper layer (11) and aluminum layer (13), heat the aluminum raw material to melt under vacuum conditions and refine and heat it to the first temperature, degrease and roughen the surface of the copper strip raw material and preheat it to the second temperature, pour the aluminum liquid at the first temperature onto one side of the copper strip raw material and cast and roll it, control the cooling rate, and form the initial composite slab. S200, Multi-stage heat treatment and rolling: The initial composite slab is placed in a protective atmosphere for a first annealing and held at the temperature for a first time; then it is cold rolled and annealed again, held at the temperature for a second time; then it is precision rolled, leveled and cut to length to the target thickness, and then annealed in the final annealing process. After being taken out of the furnace and air-cooled to room temperature, the second composite slab is obtained. S300, Heat dissipation tooth processing: Heat dissipation teeth (14) are processed on the surface of the aluminum layer side of the second composite plate to obtain the conductive busbar (10). S400, Assembly: Fix the conductive busbar (10) to the corresponding mounting platform of the three-dimensional insulating support frame (20), so that the heat dissipation teeth (14) correspond to the airflow direction of the air duct (21).

9. The method for manufacturing a copper-aluminum eutectic composite conductive bus according to claim 8, characterized in that, In S100: the first temperature is 720℃-750℃; the second temperature is 100℃-150℃; and the cooling rate is 300℃ / s-1000℃ / s.

10. The method for manufacturing a copper-aluminum eutectic composite conductive bus according to claim 8, characterized in that, In S200: the temperature for the first annealing is 250℃-300℃, and the first time is 2h-5h; the temperature for the second annealing is 300℃-350℃, and the second time is 1h-3h.